Antioxidant activity and lipid peroxidation in Artemia nauplii enriched with DHA‐rich oil emulsion and the effect of adding an external antioxidant based on hydroxytyrosol. (19th November 2015) - Viciano, Elena; Monroig, Óscar; Barata, Carlos; Peña, Carlos; Navarro, Juan Carlos
Abstract: Artemia nauplii catabolize polyunsaturated fatty acids (PUFA); in particular, they retroconvert docosahexaenoic acid (DHA, 22:6n‐3), so enrichment is a continuous quest towards increasing PUFA through the use of PUFA‐rich enrichment products. However, optimal conditions during enrichment (aeration, illumination and temperatures around 28°C) tend to accelerate autoxidation of PUFA and the formation of potentially toxic oxidation products. Water‐soluble antioxidants like the polyphenolic compound hydroxytyrosol (3, 4‐dihydroxyphenylethanol), a polar molecule found in the water fraction resulting after the milling process of olives, arise as promising compounds to prevent oxidation during Artemia enrichments. We investigated the antioxidant activity and lipid peroxidation in Artemia nauplii during enrichment and the effect of adding an external antioxidant based on hydroxytyrosol during the enrichment with a PUFA‐rich emulsion (M70). For this purpose, the activity of antioxidant enzymes (catalase, superoxide dismutase, glutathione‐S‐transferase, glutathione peroxidase), as well as lipid peroxidation, was determined in enriched and unenriched Artemia nauplii. To validate antioxidant activity and lipid peroxidation, in a first experiment, nauplii were enriched with microalgae ( Tetraselmis suecica ), yeast ( Saccharomyces cerevisiae ) and M70 emulsion. In a second experiment, enrichment with a commercial emulsion (DC Super Selco), M70, and a combination of M70 and hydroxytyrosol (Hytolive, HYT) added as an external antioxidant were performed. The combination of M70 with HYT produced the best results, in terms of activity of antioxidant enzymes. The analysis of the fatty acids from total lipids showed that the addition of hydroxytyrosol preserved the DHA percentage of enriched nauplii.